HUBUNGAN ANTARA DUKUNGAN INFORMASI SOSIAL PETUGAS KEPADA PASIEN DENGAN KEPUASAN PASIEN RAWAT INAP DI RSUD BIAK NUMFOR - Jumu, La (JURNAL EKOLOGI BIROKRASI, 2015)
The tittle of research: the relationship of social information supporting by employee to the satisfaction of staying patient in RSUD in Biak Numfor (Public Hospital of Biak Regency). Objective; to analyze the positive or the significant relationship of free variable (x) from the employee to support the social information for the bound variable (y) as the variable for the satisfaction of staying patient in RSUD in Biak Numfor (Public Hospital of Biak Regency). Hypothesis of working: (H1 or Ha) based on the result, significant test by using the test result of r accounting / r empirical â¥ r table or r theory as the following calculation r accounting = 0.275 â¥ r table = 0,245, with Î± = 0,05, then the r accounting is significant, where the conclusion of hypothesis (H1, or Ha) is : there is a significant or benefit relationship between the social information supporting from the employee for the satisfaction of staying patient in RSUD in Biak Numfor in 2015 (Public Hospital of Biak Regency). Research Methodology : by using the approach of explanative survey, the paradigm of quantitative descriptive, the method of research survey and the method of cross sectional as the way of collecting the data, the number of research sample is 66 responders with the statistic test where the simple coefficient. key words: the social information supporting, the health employee; the completeness of information, the service, and patientâs satisfaction.